Como se constitui o discurso em sala de aula em professores em início de carreira - Anderson Cezar Lobato (2015)
Considering that the practice of many newly qualified teachers is not anchored byteaching and learning theories, studied during the initial training course, thisstudy investigated which factors favor teachers in the beginning ofcareers to practice a different teaching from that they have had.For this, we rely on Vygotsky theories, which deal with the language and concept formation, converging with Bakhtin studies that deal with the verbal interaction between subjects.Also we base on the communicative approach proposed by Mortimer& Scott and in methodology used for interactions analysis that happens in classroom.Have selected, in this study, two teachers who were attending an initiation project to teaching, had no experience as a premise to enter in this project and had appeared not appropriate some contemporary trends for teaching and learning due the project participation. Were selected for these teachers, the stretches of two lessons correspondingto timesdifferent inproject participation (which call class A, closest to the beginning of project participation and class B at the end of this participation). Of selected excerpts were transcribed the speeches of teacher and students than were analyzed considering initiation types (MEHAN, 1979) done by the teachers, the space that students have in class in terms of speech, communicative approach and interaction patterns (MORTIMER and SCOTT, 2002).The selected excerpts show interaction moments between teacher and students and exemplify teachers performance in initial training. In the initial project phase were more common the triadic interaction patterns and the predominance of an authority approach, although the lessons were interactive.Also observe predominance of an initiation type choice or product. After a time of shared experiences the data showed higher presence of initiations which demand a description or explanation of processes, which favored statementscompleted, leading to increased interaction between class participants. Also observed in this study the moments occurrence in which the views of students were considered and teachers gave more voice to students valorizing what they had to say about the phenomenon or fact being studied. At such times, the class was ranked more interactive and dialogical. In order to understand how teachers justify the decision-making that have had in class, it was utilized in this study the semi-structured interviews that were recorded on video and then transcribed. During the interview, the teachers confirmed the evaluation done on their work and justified the changes in the ways of acting in classroom. Among these reasons is the formation of a reflective process on their practice that they are building. This reflection is maintained even not being more linked to the project. The perception of the relationship between theory and practice and the opportunity to carry out different lessons of those that had generated the teachers a new perspective on teaching and creating awareness importance of including students in class. They showed strong evidence that consolidated a choice made when they chose the Degree in Chemistry. With this study, can been argue about the importance of projects for initiating's teaching, when these projects build a reflected practice. To what seems, during graduation these teachers investigated had not experienced other educational opportunities and therefore not undertaken a reflective process that would enable them to choose one or other form of work. The experience lived by them served to inspire to rethink the teacher's work as to consolidate the desire to work as teachers.